TINJAUAN YURIDIS TERHADAP PERTANGGUNGJAWABAN PIDANA ANAK SEBAGAI PELAKU PENGANIAYAAN YANG MENGAKIBATKAN KEMATIAN MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Hermi Asmawati Hermi (Universitas Muhammadiyah Kotabumi, 2022)
The purpose of implementing Juvenile Criminal Justice System is actually not only aimed at imposing criminal sanctions on children alone, but is more focused as a means of supporting the realization of the welfare of children who commit crimes. The research aims to find out how the criminal responsibility of minors as perpetrators of abuse resulting in death is according to the Juvenile Criminal Justice System Act. This study uses a normative legal method with a statutory approach. The results of the study show that the criminal responsibility of children who are perpetrators of abuse that cause death must prioritizes restorative justice processes and diversion as the main options. However, if in his judgment the child perpetrator of the crime cannot be carried out, the judge must decide the case based on the provisions of the Juvenile Criminal Justice System Law.